'Killing them softly with this song ...' the literary structure of Psalm 3 and its Psalmic and Davidic contexts part II : a contextual and intertextual interpretation of Psalm 3 - Botha, Phil J.; Weber, Beat (Old Testament Essays, 2008)
In this article, the second in a series of two on Ps 3, the contribution which its immediate literary context and its heading makes to the interpretation of Ps 3 is discussed. It seems that Ps 3 is connected to its immediate neighbours, Pss 1-2 on the one hand, and Pss 4-14 on the other, with the help of key-words and shared motifs. The heading draws attention to intertextual connections it has with the narrative of Absalom's revolt in 2 Sam 15-19 and with David's song of triumph in 2 Sam 22, and through this last mentioned text also with the rest of the Psalter. Ps 3 can consequently be viewed as part of the 'overture' of the Psalter consisting of Pss 1-3, but simultaneously as the first exemplaric prayer of David which he formulated under difficult circumstances. The connections with 2 Sam 22 also suggest that the psalm can only be properly understood from the perspective of David's victory over 'all' his enemies.
free